2013
DOI: 10.1177/1087054713498932
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Barkley Deficits in Executive Functioning Scale in a College Population: Does It Predict Symptoms of ADHD Better Than a Visual-Search Task?

Abstract: This study provides evidence of validity for the BDEFS in a college sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…This absence of a strong correlation between ratings and tests reflects a lack of ecological validity of neuropsychological tests. Other studies using the BDEFS English Version have shown similar results [17][18][19][20]24,25 . For example, as found by Vasconcelos et al 26 the BIS 11 Brazilian Portuguese Version presents almost non-significant correlations with the Iowa Gambling Task, which support the theoretical and statistical difference between these types of neuropsychological methods.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…This absence of a strong correlation between ratings and tests reflects a lack of ecological validity of neuropsychological tests. Other studies using the BDEFS English Version have shown similar results [17][18][19][20]24,25 . For example, as found by Vasconcelos et al 26 the BIS 11 Brazilian Portuguese Version presents almost non-significant correlations with the Iowa Gambling Task, which support the theoretical and statistical difference between these types of neuropsychological methods.…”
Section: Discussionsupporting
confidence: 67%
“…Dehili et al 20 analyzed the capacity of BDEFS to predict symptoms of ADHD in comparison to a visual-search task in a college population. The results showed that the BDEFS is more predictive of ADHD than the task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the very strong cross-national gradient and the plausibility of this possibility, it would be valuable to carry out a cross-national comparative analysis that used objective performance-based neurocognitive tests to evaluate prevalence of the cognitive deficits underlying adult ADHD rather than relying only on self-report assessments. It is noteworthy in this regard that performance-based neurocognitive tests have been used in a number of recent studies of adult ADHD (e.g., Dehili et al 2013; Micoulaud-Franchi et al 2016; Surman et al 2015) and could be used in parallel in community surveys using recently developed technology for administering such tests in web-based surveys (www.manybrains.net). It is important to note in this regard, though, that the neurocognitive tests studied in adult ADHD up to now have been heterogeneous, in many cases only weakly correlated with each other, and non-specific for adult ADHD, making it unclear whether this line of research has yet progressed sufficiently to warrant implementing such tests in large-scale cross-national community epidemiological surveys.…”
Section: Discussionmentioning
confidence: 99%